A manufacturing process for a highly wear-resistant chain pin
By adopting two carbon-nitride co-penetration processes with different heating temperatures and fine grinding treatment steps in the carbon-nitride co-penetration process of the chain pin shaft, a fine and diffuse distribution of carbon-nitride co-penetration layer and a fine needle-shaped martensite mixed structure is formed, which solves the problems of insufficient surface hardness and low wear resistance of the chain pin shaft in the prior art, and significantly improves the subsurface hardness and wear resistance of the subsurface layer.
Patent Information
- Application Number
- CN202310329218.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-30
AI Technical Summary
The carbon-nitrogen co-permeation treatment process of existing chain pins has problems such as insufficient surface hardness and low wear resistance, which is mainly due to the failure to fully eliminate non-equine tissue and surface porous defects caused by one-stage heat treatment.
Two carbon-nitrogen co-permeation processes with different heating temperatures were adopted, and the fine grinding treatment steps were added in the middle to form a carbon-nitrogen co-permeation layer with a small surface and a fine needle-like martensite mixed structure, reducing the residual austenite content of the surface layer, and achieving hardness gradient control in the high hardening zone above 680HV of the subsurface layer within the range of 30% to 70% effective hardening layer.
The sub-surface hardness and wear resistance of the chain pin shaft are significantly improved, the surface hardness is not less than 800HV, the hardening layer depth is not less than 0.5mm, and the high hardening zone depth at 680HV of the sub-surface layer is not less than 0.15mm, meeting the fatigue resistance and wear resistance requirements under complex service conditions.
Smart Images

Figure HDA0004154333030000011 
Figure HDA0004154333030000012 
Figure HDA0004154333030000021
Abstract
Description
Technical Field
[0001] The invention relates to a manufacturing process of a highly wear-resistant chain pin shaft. Background Art
[0002] In the chain industry, the carbonitriding heat treatment process is an important part of the manufacturing process of chain pins. It mainly uses high-temperature heating to allow carbon atoms and nitrogen atoms to penetrate into the interior of the pin, and then achieves the effect of improving the surface hardness and core hardness of the chain pin through quenching.
[0003] At present, most of the carbonitriding treatment processes used for chain pins are one-stage heat treatment processes, that is, high-temperature heating is used to allow carbon atoms and nitrogen atoms to penetrate into the interior of the pins, and then direct quenching is performed at this temperature. It should be pointed out that after the traditional one-stage heat treatment, the surface of the parts often produces non-horse tissue of about 10 to 20 μm, and the surface porous defects caused by the wire drawing or cold heading process of the raw materials have not been fully eliminated. There are also uneven carburizing layers caused by insufficient heat treatment heating and unstable carburizing atmosphere, which seriously restrict the improvement of the wear resistance level of the chain.
[0004] The Chinese patent with the announcement number CN110144546 A discloses a carbonitriding process for engine timing chain pins, which discloses a cycle furnace processing process. The chain pins used in the disclosed technology do not fully consider the impact of the surface quality of the parts and the improvement of the wear resistance of the chain, and do not involve the control of the sub-surface hardness gradient of the parts. The surface hardness described in the above product embodiment is 785HV, 750HV, and 765HV. It can be seen that the surface hardness of the parts needs to be improved. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a manufacturing process for a highly wear-resistant chain pin shaft. Through the carbonitriding process, a fine and diffusely distributed carbonitriding layer and a fine needle-shaped martensite mixed structure are obtained on the surface, and the residual austenite content in the surface structure is reduced, so that the high hardening zone above 680HV in the sub-surface is within the range of 30% to 70% of the effective hardening layer, thereby significantly improving the sub-surface hardness and wear resistance of the parts.
[0006] To achieve the above object, the technical solution adopted by the present invention is a manufacturing process of a high wear-resistant chain pin, comprising the following steps:
[0007] Step A, pre-hardening treatment: put the chain pin into a rotary resistance furnace for carbonitriding, the carburizing medium is propane, methanol and ammonia, the heating temperature is 870-890°C, the holding time is controlled at 110-130 minutes, and an effective hardened layer with a depth of not less than 0.5 mm is formed. After the holding time is reached, quenching is carried out and the chain pin is quenched into a 40-80°C oil tank for cooling;
[0008] Step B, low temperature tempering: reheat the quenched pin to 190-210°C for tempering, with a holding time of 120-150 minutes;
[0009] Step C, fine grinding: fine grinding is performed using a grinder, with a grinding depth of no more than 0.05 mm, so that the surface roughness is controlled below Ra0.2; and
[0010] Step D, low-temperature carbonitriding: the finely ground chain pin shaft enters a controlled atmosphere continuous mesh belt furnace, and in the nitriding stage, a large amount of ammonia is introduced at a constant carbon potential of 0.7-0.9%, and maintained for 120-140 minutes to form a carbonitriding layer with a depth of not less than 0.15 mm. The temperature of the front zone and the middle zone of the mesh belt furnace is controlled at a low temperature of 820-840° C., and the end zone of the mesh belt furnace is set as a quenching zone, and the temperature of the quenching zone is controlled to be high temperature. After the holding time is reached, the chain pin shaft is directly quenched into a quenching oil tank for cooling, and the temperature of the oil tank is controlled at 40-80° C.; in the tempering stage, the chain pin shaft enters a continuous tempering mesh belt furnace, is heated to a temperature of 150-170° C., and is maintained for 120-150 minutes before being taken out of the furnace and air-cooled to room temperature.
[0011] The quenching temperature described in step D is a high temperature, and the heat treatment temperature AC3+ (40-70°C) corresponding to the material grade of the processed parts is controlled as the heating temperature. The quenching temperature of general low-carbon alloy steel can be selected from 850-870°C. After quenching, a fine, diffusely distributed carbonitriding layer and a fine needle-shaped martensite mixed structure are obtained, and the depth of the high hardening zone at 680HV from the surface layer to the sub-surface layer is within the effective hardening layer range of 30% to 70%. After the parts are quenched, the surface hardness obtained is not less than 800HV, the depth of the hardened layer is not less than 0.5mm, and the depth of the high hardening zone at 680HV of the sub-surface layer is not less than 0.15mm, so that the parts have higher wear resistance. Low-temperature tempering of the quenched parts can eliminate the surface stress of the parts and improve the toughness. Its role can also effectively reduce the residual austenite content on the surface of the workpiece and reduce the deformation of the parts.
[0012] In one embodiment of the present invention, in step A, the flow rate of carburizing medium propane is 160-180 L / H, the flow rate of methanol is 3-5 ml / min, and the flow rate of ammonia is 80-120 L / H.
[0013] In one embodiment of the present invention, the equipment in step C is a continuously controllable segmented high-precision centerless grinder, and the grinding wheel used is a 220-mesh rubber grinding wheel.
[0014] In one embodiment of the present invention, the enriched gas in step D is propane.
[0015] In one embodiment of the present invention, the carrier gas in step D is methanol cracking gas, and the methanol flow rate is set to 6-8 L / H; at the same time, the volume of ammonia introduced is 6-9% of the volume of the carrier gas, and the ammonia flow rate is 600-900 L / H.
[0016] In one embodiment of the present invention, the high temperature of the quenching zone in step D is controlled as the heating temperature according to the heat treatment AC3+ (40-70° C.) corresponding to the material grade of the chain pin.
[0017] In one embodiment of the present invention, in step D, a mixed structure of a fine, diffusely distributed carbonitriding layer and fine needle-shaped martensite is obtained after quenching.
[0018] In one embodiment of the present invention, the chain pin is made of low-carbon alloy structural steel.
[0019] This technical solution has the following beneficial effects:
[0020] Compared with the prior art, the heat treatment process of the present invention adopts two carbonitriding processes with different heating temperatures, and adds a surface grinding process in the middle, which effectively improves the surface roughness quality of the parts. Specifically, the present invention first performs high-temperature carbonitriding treatment on the parts, aiming to quickly and evenly infiltrate saturated carbon atoms and nitrogen atoms, ensuring that the workpiece has a uniform and sufficiently deep effective hardened layer, and the quenching and tempering after carbonitriding improve the surface hardness and toughness of the pin shaft, so that under the conditions of precision grinding process, it is beneficial to improve the surface quality level of the parts, and no grinding cracks will be generated. Further, after completing the first carbonitriding treatment, the non-horse structure and uneven infiltration layer left on the surface can be removed, leaving an effective hardened layer with a concentration of more than 0.7%, and then a second low-temperature nitriding treatment is carried out on the basis of this hardened layer, and a high concentration of nitrogen atoms is infiltrated to form a more dense carbonitriding compound, enhance the wear resistance of the parts, and the quenching and tempering process after nitriding eliminates the residual stress of the parts, further improves the toughness, so that the chain pin shaft meets the complex service conditions and has higher fatigue resistance and wear resistance.
[0021] The present invention adopts two different carbonitriding processes at high temperature and low temperature, and adds a continuous segmented grinding process in between, which can effectively reduce the deformation of parts while retaining a good hardened layer structure. This is an ideal process innovation for improving the manufacturing accuracy of the chain and can be used as a preferred manufacturing process for high wear-resistant chains.
[0022] Furthermore, the present invention controls the heating temperature and the flow rate of ammonia gas, the nitriding medium, in the two carbonitriding processes differently. On the one hand, it is considered that low-carbon alloy structural steel is suitable for low-temperature nitriding, which is beneficial to improving the efficiency of nitriding layer formation, so that the carbides with a carbon concentration gradient of 0.7% in the sub-surface layer slowly diffuse and translate toward the center. On the other hand, increasing the heating temperature during the quenching stage is beneficial to improving the hardenability of different materials, so that the sub-surface hardness gradient meets the process expectations, thereby breaking through the technical bottleneck of the traditional carbonitriding process.
[0023] In summary, the present invention has the advantages of refining the surface carbonitriding layer and the needle-shaped martensite mixed structure, reducing the residual austenite content in the surface layer, realizing a heat treatment process with flexible control of the sub-surface hardness gradient, and improving the surface hardness and wear resistance of the chain pin shaft. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the surface metallographic structure spectrum of the workpiece of Example 1 (traditional process);
[0025] Figure 2 It is a metallographic structure spectrum of the surface layer of the workpiece of the embodiment of the present invention;
[0026] Figure 3 is the hardness gradient curve of the embodiment of the present invention and the comparative example 1;
[0027] Figure 4 It is a comparison chart of the wear elongation of the workpieces of Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0028] Below is a combination of the embodiments and the attached Figures 1 to 4 The present invention is further described.
[0029] Comparative Example 1
[0030] A manufacturing process for a wear-resistant chain pin comprises the following steps:
[0031] The first process: put the chain pin into a rotary resistance furnace to obtain an effective hardened layer of a certain depth. The carburizing medium is propane, methanol, and ammonia. The heating temperature is 840-860℃, and the holding time is controlled at 120-150 minutes to form an effective hardened layer with a depth of not less than 0.5mm. After the holding time is reached, quenching is carried out and quenched into a 40-80℃ oil tank for cooling. The flow rate of carburizing medium propane is 160-180L / H, the flow rate of methanol is 3-5ml / min, and the flow rate of ammonia is 100-140L / H.
[0032] The second process: reheat the quenched pin shaft to 170-190°C for tempering. The tempering holding time is 90-120 minutes. The tempering equipment can be a rotary resistance furnace or a mesh belt tempering furnace.
[0033] The metallographic structure of the surface treated by traditional technology is as follows Figure 1 As shown, there are a lot of non-martensitic tissues from the surface to the depth of 14um. Under a 4000x electron microscope, it was observed that the length of the non-martensitic needles was about 3.72um to 4.35um, and the surface was a second-level needle-shaped martensitic structure.
[0034] Example 1
[0035] A manufacturing process for a highly wear-resistant chain pin comprises the following steps:
[0036] Step A, high temperature carbonitriding, placing the chain pin into a rotary resistance furnace, the carburizing medium is propane, methanol, ammonia, the heating temperature is 870°C, the holding time is controlled at 130 minutes, and quenching is performed after the holding time is reached, that is, quenching into a 40°C oil tank for cooling;
[0037] Step B, low temperature tempering after quenching: reheat the quenched pin to 190°C for tempering, and keep the temperature for 120 minutes;
[0038] Step C, fine grinding, using a continuously controllable segmented high-precision centerless grinder, with a grinding depth of 0.05 mm and a surface roughness of Ra0.15;
[0039] Step D, low-temperature carbonitriding, the parts enter a controlled atmosphere continuous mesh belt furnace, in the nitriding stage, a large amount of ammonia is introduced at a constant carbon potential of 0.7%, and the temperature of zones 1 to 4 of the mesh belt furnace is controlled at a low temperature of 820°C, 820°C, 820°C, and 830°C respectively; the temperature of zone 5 of the mesh belt furnace is set to a high temperature of 850°C, and after the holding time is reached, it is directly quenched into a quenching oil tank for cooling, and the temperature of the oil tank is controlled at 50°C; in the tempering stage, the pin enters a continuous tempering mesh belt furnace, the temperature is raised to 150°C, and it is kept for 120 minutes before being taken out of the furnace and air-cooled to room temperature.
[0040] In step A, the flow rate of carburizing medium propane is 160 L / H, the flow rate of methanol is 3 ml / min, and the flow rate of ammonia is 80 L / H;
[0041] The equipment in step C is a high-precision centerless grinder, and the grinding wheel is a 220-mesh rubber grinding wheel.
[0042] In step D, the enriched gas is propane, and the flow rate of propane is automatically adjusted according to the carbon potential;
[0043] When the carrier gas in step D is methanol cracking gas, the methanol flow rate is set to 6 L / H; at the same time, the flow rate of ammonia gas introduced into the nitriding medium is set to 600 L / H;
[0044] The high temperature in step D, after quenching, obtains a fine, diffusely distributed carbonitriding layer and a fine needle-shaped martensite mixed structure on the surface, and the depth of the high hardening zone above 680HV is 0.35mm, and the depth of the effective hardening layer above 550HV is 0.58mm, and the depth of the high hardening zone accounts for 60% of the entire effective hardening layer depth.
[0045] In this embodiment, the material of the processed chain pin is 30CrMnTi.
[0046] Step A and step B together form a high-temperature carbonitriding stage, which is mainly used to quickly and evenly infiltrate carbon atoms and nitrogen atoms to ensure uniform thickness of the carburized layer of the workpiece. The purpose of quenching is to transform the supercooled austenite into martensite so that the workpiece surface obtains a martensitic structure. Since the workpiece surface obtains a hard and brittle martensitic structure after carburizing and quenching, carburizing and tempering treatment can greatly improve the hardness, wear resistance and toughness of the parts.
[0047] Step C: Precision grinding the surface of the parts processed in steps A and B, removing the non-marine tissue on the surface, retaining a uniform effective hardened layer, and improving the surface quality, so that the surface roughness is not greater than Ra0.2;
[0048] Step D is the low-temperature carbonitriding stage, which is used to infiltrate more nitrogen atoms on the basis of the high-temperature nitriding layer, forming a denser carbonitride layer on the sub-surface of the part to enhance its wear resistance.
[0049] The surface metallographic structure of the product after treatment in this embodiment is as follows Figure 2 As shown, there is no obvious non-martensite structure on the surface, the martensite needle lengths are 1.36um, 1.85um, and 2.31um, and the surface is level 1 needle-shaped martensite structure.
[0050] Example 2
[0051] A manufacturing process for a highly wear-resistant chain pin comprises the following steps:
[0052] Step A, high temperature carbonitriding, placing the chain pin into a rotary resistance furnace, the carburizing medium is propane, methanol, ammonia, the heating temperature is 890°C, the holding time is controlled at 110 minutes, and quenching is performed after the holding time is reached, that is, quenching into an 80°C oil tank for cooling;
[0053] Step B, low temperature tempering after quenching: reheat the quenched pin to 210°C for tempering, and keep the temperature for 150 minutes;
[0054] Step C, fine grinding, using a continuously controllable segmented high-precision centerless grinder, with a grinding depth of 0.05 mm and a surface roughness of Ra0.16;
[0055] Step D, low-temperature carbonitriding, the parts enter a controlled atmosphere continuous mesh belt furnace, in the nitriding stage, a large amount of ammonia is introduced at a constant carbon potential of 0.9%, and the temperature of zones 1 to 4 of the mesh belt furnace is controlled at a low temperature, which are set to 840°C, 840°C, 840°C, and 850°C respectively; the end zone of the mesh belt furnace is set as a quenching zone, and the temperature of zone 5 is controlled to be a high temperature, which is set to 870°C. After the holding time is reached, the parts are directly quenched into a quenching oil tank for cooling, and the temperature of the oil tank is controlled to be 80°C; in the tempering stage, the pin enters a continuous tempering mesh belt furnace, the temperature is raised to 170°C, and it is kept for 150 minutes before being taken out of the furnace and air-cooled to room temperature.
[0056] In step A, the flow rate of carburizing medium propane is 180 L / H, the flow rate of methanol is 5 ml / min, and the flow rate of ammonia is 120 L / H;
[0057] The equipment in step C is a high-precision centerless grinder, and the grinding wheel is a 220-mesh rubber grinding wheel.
[0058] In step D, the enriched gas is propane, and the flow rate of propane is automatically adjusted according to the carbon potential;
[0059] When the carrier gas in step D is methanol cracking gas, the methanol flow rate is set to 8 L / H; at the same time, the flow rate of ammonia gas introduced into the nitriding medium is set to 900 L / H;
[0060] The high temperature in step D, after quenching, obtains a fine, diffusely distributed carbonitriding layer and a fine needle-shaped martensite mixed structure on the surface, and the depth of the high hardening zone above 680HV is 0.45mm, and the depth of the effective hardening layer above 550HV is 0.68mm, and the depth of the high hardening zone is 66% of the effective hardening layer depth.
[0061] In this embodiment, the material of the processed chain pin is 30CrMnTi.
[0062] Example 3
[0063] A manufacturing process for a highly wear-resistant chain pin comprises the following steps:
[0064] Step A, high temperature carbonitriding, placing the chain pin into a rotary resistance furnace, the carburizing medium is propane, methanol, ammonia, the heating temperature is 880°C, the holding time is controlled at 120 minutes, and quenching is performed after the holding time is reached, that is, quenching into a 40°C oil tank for cooling;
[0065] Step B, low temperature tempering after quenching: reheat the quenched pin to 200°C for tempering, and keep the temperature for 130 minutes;
[0066] Step C, fine grinding, using a continuously controllable segmented high-precision centerless grinder, with a grinding depth of 0.05 mm and a surface roughness of Ra0.12;
[0067] Step D, low-temperature carbonitriding, the parts enter a controlled atmosphere continuous mesh belt furnace, in the nitriding stage, a large amount of ammonia is introduced at a constant carbon potential of 0.8%, and the temperature of zones 1 to 4 of the mesh belt furnace is controlled at a low temperature, which are set to 830°C, 830°C, 830°C, and 840°C respectively; the end zone of the mesh belt furnace is set as a quenching zone, and the temperature of zone 5 is controlled to be a high temperature, which is set to 860°C. After the holding time is reached, the parts are directly quenched into a quenching oil tank for cooling, and the temperature of the oil tank is controlled at 60°C; in the tempering stage, the pin enters a continuous tempering mesh belt furnace, the temperature is raised to 160°C, and the temperature is maintained for 130 minutes before being taken out of the furnace and air-cooled to room temperature.
[0068] In step A, the flow rate of carburizing medium propane is 170 L / H, the flow rate of methanol is 4 ml / min, and the flow rate of ammonia is 100 L / H;
[0069] The equipment in step C is a high-precision centerless grinder, and the grinding wheel is a 220-mesh rubber grinding wheel.
[0070] In step D, the enriched gas is propane, and the flow rate of propane is automatically adjusted according to the carbon potential;
[0071] When the carrier gas in step D is methanol cracking gas, the methanol flow rate is set to 7 L / H; at the same time, the flow rate of ammonia gas introduced into the nitriding medium is set to 800 L / H;
[0072] The high temperature in step D, after quenching, obtains a fine, diffusely distributed carbonitriding layer and a fine needle-shaped martensite mixed structure on the surface, the depth of the high hardening zone above 680HV is 0.3mm, and the depth of the effective hardening layer above 550HV is 0.59mm, and the depth of the high hardening zone accounts for 50% of the entire effective hardening layer depth.
[0073] In this embodiment, the material of the processed chain pin is 30CrMnTi.
[0074] The present invention has the characteristics of using a higher temperature in the high-temperature nitriding stage of the chain pin after a composite treatment, and a longer heating time under the conditions of carburizing media propane, methanol and ammonia, so that the alloy elements on the surface of the pin are fully austenitized to form an effective hardened layer of a certain depth; and after the above-mentioned pre-hardening treatment, the surface of the part is finely ground to remove defects such as non-martensitic structures on the surface; finally, after the low-temperature nitriding stage, a certain proportion of ammonia flow and a longer diffusion time are introduced to form a high hardened layer of sufficient depth on the surface of the pin, and a fine and diffusely distributed carbonitriding layer and a fine needle-shaped martensitic mixed structure are obtained on the surface. By selecting a suitable quenching temperature, the high hardening area above 680HV on the sub-surface can be arbitrarily adjusted within the range of 30% to 70% of the effective hardened layer, thereby achieving the purpose of the present invention, significantly raising the sub-surface hardness gradient of the pin, and greatly improving the wear resistance of the chain.
[0075] The hardness of different processing methods is as follows Figure 3 As shown: the chain pin shaft is processed by the embodiments 1, 2, and 3 of the present invention, and its surface hardness reaches 850HV0.1 or more, especially the sub-surface hardness gradient generally reaches 680HV or more, and the high hardening area after lifting can withstand the impact load for a longer time, thereby effectively improving the product's fatigue spalling and wear resistance. This process is applied to the pin shaft of the precision roller chain for transmission. After experiments, the wear resistance of the product is greatly improved.
[0076] The hardness of the pins treated by different processes in Examples 1, 2, 3 and Comparative Example 1 of the present invention is tested. The measured results are as follows: Figure 3 As shown, the horizontal axis represents the distance from the surface of the part to the surface, and the vertical axis is the measured microhardness value (unit: HV0.3). The specific data are: the surface hardnesses of the three pins treated by the embodiment of the present invention are 869HV0.3, 890HV0.3, and 858HV0.3, respectively, and the surface hardness of the parts treated in comparative example 1 is 630HV0.3; it can be seen that the surface hardness of the chain pin treated by the manufacturing process of the present invention is significantly higher than the hardness of the comparative example 1 treated by the traditional process, and the sub-surface hardness of the chain pin treated by the process of the present invention is more than 680HV, and the depth reaches more than 0.3mm, which further shows that the present invention effectively improves the hardness gradient of the product, which is beneficial to achieving higher wear resistance.
[0077] Table 1 Pin hardness measurement data with different process treatments
[0078] Distance from surface 0 50 100 150 200 300 400 500 600 700 800 900 1000 1200 1300 Comparative Example 1 630 621 583 550 503 450 445 427 418 415 415 420 424 418 418 Example 1 869 822 792 787 772 742 655 585 562 524 492 464 457 452 452 Example 2 890 857 838 792 763 729 701 652 576 542 502 492 479 463 463 Example 3 858 806 788 756 732 681 640 574 558 520 495 470 471 467 467
[0079] Convert the above measurement data into a hardness gradient curve for comparison. See the attachment for details. Figure 3By comparing the hardness gradient curves of the embodiment of the present invention with that of comparative example 1, it can be further found that the surface hardness and subsurface hardness of the embodiment are significantly improved compared with those of the comparative example.
[0080] The two chains treated by the process of Example 3 of the present invention and the process of Comparative Example 1 were subjected to a 1000-hour wear elongation test on a special chain test bench CWP-5000S, with the driving wheel rotating at 210 rpm. The test results are as follows: Figure 4 As shown, the horizontal axis represents time (unit: hour), and the vertical axis represents wear elongation (%). After reaching 660 hours, the wear elongation of comparative example 1 is 0.6%, while under the same test time conditions, the elongation of embodiment 3 is only 0.15%. The results show that the wear resistance of the present invention is improved by more than 4 times compared with the traditional process. As the test continues, it can be clearly found that the wear elongation of the chain manufactured by the present invention after 1000 hours is lower than the wear elongation of the traditional process, that is, the present invention has better wear resistance.
[0081] In addition, a large number of tests and studies have shown that the residual austenite on the surface of the parts is significantly reduced after the implementation of the present invention, and the wear resistance of the chain is significantly improved after the subsurface hardness gradient is raised, breaking through the technical bottleneck of the traditional carbonitriding process. The manufacturing process of the present invention can also be applied to other service conditions to increase the service life.
[0082] The above specific embodiments are only used to illustrate the present invention rather than to limit the present invention. Any changes and substitutions made to the present invention without creative work within the scope of protection of the present invention and the claims shall fall within the scope of protection of the patent of the present invention.
Claims
1. A manufacturing process for a highly wear-resistant chain pin, characterized in that: The steps include: Step A, pre-hardening treatment: put the chain pin into a rotary resistance furnace for carbonitriding, the carburizing medium is propane, methanol and ammonia, the heating temperature is 870-890°C, the holding time is controlled at 110-130 minutes, and an effective hardened layer with a depth of not less than 0.5 mm is formed. After the holding time is reached, quenching is carried out and the chain pin is quenched into a 40-80°C oil tank for cooling; Step B, low temperature tempering: reheat the quenched pin to 190-210°C for tempering, with a holding time of 120-150 minutes; Step C, fine grinding: fine grinding is performed using a grinder, with a grinding depth of no more than 0.05 mm, so that the surface roughness is controlled below Ra0.2; and Step D, low-temperature carbonitriding: the finely ground chain pin shaft enters a controlled atmosphere continuous mesh belt furnace, and in the nitriding stage, a large amount of ammonia is introduced at a constant carbon potential of 0.7-0.9%, and maintained for 120-140 minutes to form a carbonitriding layer with a depth of not less than 0.15 mm, and the temperature of the front zone and the middle zone of the mesh belt furnace is controlled at a low temperature of 820-840°C, and the end zone of the mesh belt furnace is set as a quenching zone, and the temperature of the quenching zone is controlled to be high temperature. After the holding time is reached, it is directly quenched into the quenching oil tank for cooling, and the temperature of the oil tank is controlled at 40-80°C; in the tempering stage, the chain pin shaft enters the continuous tempering mesh belt furnace, and the temperature is raised to 150-170°C, and maintained for 120-150 minutes before being taken out of the furnace and air-cooled to room temperature; The high temperature of the quenching zone in step D is controlled as the heating temperature according to the heat treatment AC3+ (40~70℃) corresponding to the material grade of the chain pin.
2. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: In step A, the flow rate of carburizing medium propane is 160~180L / H, the flow rate of methanol is 3~5ml / min, and the flow rate of ammonia is 80~120L / H.
3. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: The equipment in step C is a continuously controllable segmented high-precision centerless grinder, and the grinding wheel used is a 220-mesh rubber grinding wheel.
4. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: In step D, the enriched gas is propane.
5. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: The carrier gas in step D is methanol cracking gas, the methanol flow rate is set to 6-8 L / H, and the ammonia flow rate is 600-900 L / H.
6. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: The material of the chain pin is low-carbon alloy structural steel. The temperature of the quenching zone in step D is high temperature, and the quenching temperature of the low-carbon alloy steel is 850-870°C.
7. The manufacturing process of the high wear-resistant chain pin according to claim 1, characterized in that: In step D, after quenching, a mixed structure of a fine, diffusely distributed carbonitriding layer and fine needle-shaped martensite is obtained.
Citation Information
Patent Citations
Manufacturing process of high-abrasion-resistance chain
CN105088133A
Heat treatment method of low-carbon alloy steel chain pin shaft
CN107345268A
Carbonitriding process for engine timing chain pin shaft
CN110144546A